Comparative Genomics and Characterisation of the Role of Saccharomyces cerevisiae Respiration in the Fermentation of Chinese Steamed Bread - Yawen Gao; Yufeng Guo; Jianing Pang; Mingkai Liu; Tengdan Yuan; Qinhong Wang; Jingsheng Liu (Journal of Fungi)
The genetic composition of Saccharomyces cerevisiae and its various phenotypes during fermentation significantly correlate to the quality of Chinese steamed bread (CSB). However, the systematic correlation between different S. cerevisiae and CSB has not been fully elucidated. Herein, we characterised CSBs prepared with 36 isolates of S. cerevisiae (designated S1–S36) to comparatively evaluate their correlations. CSBs 1, 2, 13, 21, 25 and 33 exhibited suitable total titratable acidity (TTA) values, pH values and large specific volumes. Texture analysis showed that CSBs 1, 25 and 33 exhibited higher springiness and cohesiveness values. CSBs 8, 25 and 33 exhibited low hardness, gumminess and chewiness values. At the micro level, CSBs 1, 25 and 33 showed a loose reticular structure with large holes and in which starch particles wrapped into gluten protein. Fifty-nine volatile flavour compounds belonging to six categories were determined in 10 selected CSBs, and CSBs 1, 25 and 33 contained more flavour and balanced substance categories. In addition, comparative genomic analysis revealed 33 non-synonymous mutations in the three strains with strong fermentation ability (S1, S25 and S33) and the three strains with weak fermentation ability (S18, S20 and S35) involving 19 genes, including: the respiration-related genes COS5, COS8 and COX10; the starch metabolism transcription factor MSS11; the general transcription factor SPT8; the cell aggregation-related gene FLO1 and the transporter gene SEO1. Other genes with different genotypes were also enriched in respiration-related gene ontology terms. These data offer preliminary experimental evidence regarding the application of S. cerevisiae S1, S25 and S33 in fermented foods derived from grains.